Monitoring seismic velocity changes in the Dongtan Coal Mine using ambient noise correlationKey points - Chao Kong; Kai Zhan; Xiaotao Wen; Ping Song; Lianhai Zhang; Hanying Ding (Earthquake Science)
This study analyzed ambient seismic noise using the MSNoise package to monitor temporal changes in the underground seismic wave velocity in Mining Area 6 of the Dongtan Coal Mine in China. The data was recorded continuously over 76 days by 7 three-component stations and 10 single-component microseismic stations deployed in Dongtan Coal Mine, with station spacing ranging from 0.1 km to approximately 3 km. Using the causal and non-causal components of the Z-component cross-correlation function, along with moving-window cross-spectrum analysis and cumulative calculations with a 5-day window overlay, stable seismic velocity changes were obtained in the frequency band of 0.1 to 2 Hz. We found a correlation between the timing of average velocity changes and seismic events caused by underground mining processes. In particular, when the relative seismic velocity increased by 0.23%, larger energy minequakes typically occurred. This study shows that ambient noise correlation has great potential for predicting minequakes, guiding pressure-relief production, and providing warnings about the impact of overburden pressure.